Inji Efflatoun entre le pinceau et la plume : « L’exposition de la révolutionnaire » - Nadine Atallah (Les Cahiers de l'École du Louvre)
Inji Efflatoun (1924–1989) organized her first solo exhibition at the ADAM Gallery in Cairo in March 1952. A leading figure in modern Egyptian art, Efflatoun made a name for herself with her dual career as a painter and Marxist, feminist and anti-colonialist activist. While pursuing her artistic training, she organised her exhibition against the backdrop of the Suez Crisis, which heralded the 23 July Revolution and accelerated the struggles for national independence. A study of Efflatoun’s artworks, which denounce the ravages of colonialism on the most disadvantaged segments of the population, particularly rural women, reveals the discursive strategies developed by the artist to disseminate her opinions. By observing the to-and-fro between her paintings and her writings, it is possible to understand the March 1952 exhibition as a manifesto for art committed to the society she lived in.